MOBILE TOURISM RESEARCH AND PRACTICES: A COMPREHENSIVE BIBLIOMETRIC EXPLORATION AND FUTURE STUDY DIRECTION - Shamsul Arrieya bin Ariffin, Norhisham bin Mohamad Nordin (Tanjung Malim, 2024)
MOBILE TOURISM RESEARCH AND PRACTICES: A COMPREHENSIVE BIBLIOMETRIC EXPLORATION AND FUTURE STUDY DIRECTION by Shamsul Arrieya bin Ariffin, Norhisham bin Mohamad Nordin